Pengaruh Kualitas Pelayanan terhadap Kepuasan Masyarakat Nagari Pitalah Kecamatan Batipuh - Yusra Yazit; Dasman Lanin (Lembaga Yasin AlSys, 2025)
Public service is a crucial factor in the government’s efforts to meet the needs and expectations of society. However, challenges such as slow service, convoluted procedures, and limited facilities are still commonly encountered in practice, including in Nagari Pitalah, Batipuh Subdistrict, Tanah Datar Regency, which has led to low levels of community satisfaction. This study aims to analyze the influence of service quality on community satisfaction in the area. A quantitative method with an associative approach was employed. The study population consisted of 698 household heads, with a sample of 254 respondents determined using Slovin’s formula at a 5% margin of error. Sampling was conducted through proportional stratified random sampling, and data were collected via questionnaires and analyzed using simple linear regression with SPSS version 27. The results show that service quality has a positive and significant effect on community satisfaction, with a t-value of 8.377 and a significance level of 0.000 (p < 0.05). The coefficient of determination (R²) of 0.218 indicates that service quality contributes 21.8% to community satisfaction. The regression equation obtained is Y = 15.368 + 0.350X. These findings confirm that the better the service quality provided by nagari officials, the higher the level of community satisfaction. The practical implications of this study emphasize the importance of improving staff competence, enhancing infrastructure, and implementing responsive and accountable public service standards to deliver high-quality and satisfactory services.